Lymphoepithelial Subtype of Oral Squamous Cell Carcinoma: Report of an EBV-Negative Case and Literature Review - Rodopi Emfietzoglou; Efstathios Pettas; Maria Georgaki; Erofili Papadopoulou; Vasileios Ionas Theofilou; Nikolaos Papadogeorgakis; Evangelia Piperi; Marcio Ajudarte Lopes; Nikolaos G. Nikitakis (MDPI AG, 2022)
Lymphoepithelial carcinoma (LEC) of the oral mucosa is a rare histopathologic subtype of squamous cell carcinoma (SCC), which shares morphologic similarities with nasopharyngeal carcinoma (NPC), non-keratinizing undifferentiated subtype. The admixture of neoplastic epithelial tumor cells and a dense lymphoplasmacytic infiltrate makes microscopic diagnosis challenging. LEC etiopathogenesis has been variably associated with Epstein-Barr virus (EBV) infection, depending on the specific anatomic location and racial predilection, with a higher incidence in endemic populations. Although described in several subsites of the head and neck region, including the major salivary glands, the oral mucosa is considered an infrequent location for LEC development, deriving either from minor salivary glands (MSGs) or the surface epithelium. Herein, we report a rare case of an EBV-negative LEC arising from the oral surface epithelium, presenting as gingival swelling, and review the pertinent English-language literature, which revealed only 26 previously reported oral LECs. Our case is only the fourth oral LEC originating from the surface epithelium and the first one to affect the gingiva.